Biological Self‐Arrangement of Fiber Like Aragonite and Its Effect on Mechanical Behavior of Veined rapa whelk Shell. Issue 10 (8th July 2015) - Ji, Hong‐Mei; Jiang, Yun; Yang, Wen; Zhang, Guang‐Ping; Li, Xiao‐Wu
Abstract : The microstructures of Veined rapa whelk shell were characterized, and a series of compression tests were carried out on the shell with the compressive loading direction making different angles (0°, 30°, 60° and 90°) with the shell spiral lines. Weibull analysis of the experiment results shows that the compressive strength is generally the highest for the sample with 0°‐orientation but the lowest for that with 60°‐orientation, which means that the strength shows an obvious anisotropy and the strongest orientation represents the direction parallel to the spiral lines of the shell. Such a phenomenon is closely related to the distinctive microscopic arrangements of different‐order aragonite lamellae. The interfaces of different‐level lamellae in the adjacent macro‐layers yield effects on the mechanical behavior of the shell in a coordinated fashion.